CuS–Pt(iv)–PEG–FA nanoparticles for targeted photothermal and chemotherapy. Issue 35 (23rd August 2016) - Bi, Huiting; Dai, Yunlu; Xu, Jiating; Lv, Ruichan; He, Fei; Gai, Shili; Yang, Dan; Yang, Piaoping
Abstract : CuS–Pt(iv ) nanoparticles exhibited high in vitro and in vivo anti-tumor efficiency, which was caused by the integrated Pt drug-induced chemotherapy and CuS nanoparticle-mediated photothermal therapy (PTT) upon irradiation with near infrared (NIR) light. Abstract : Platinum (Pt)(iv ) pro-drugs, which can be reduced to highly cytotoxic Pt(ii ) by high concentrations of glutathione (GSH) in cancer cells, offer a new approach to defense against tumors. A carrier with controlled release and targeted functions is essential to determine its final anticancer efficiency. In this study, we report a targeted drug delivery system by fabricating CuS–Pt(iv )–PEG–FA nanoparticles (CuS–Pt(iv ) NPs) that integrates Pt drug-induced chemotherapy and CuS nanoparticles-mediated photothermal therapy (PTT) under near infrared (NIR) light irradiation. The attached PEG and folic acid (FA) molecules endow the system with high biocompatibility and targeted property. The release of Pt was up to 84.4% in the presence of GSH in the tumor cells due to the reduction property of GSH. Combined with the photothermal effect with high photothermal conversion efficiency (32.1%) upon NIR light irradiation, a remarkable tumor inhabitation efficacy was been achieved. The in vitro assay manifested that CuS–Pt(iv ) NPs can kill more cancer cells than that of DSP and cisplatin; the in vivo results indicate that the group treated with intravenous injection of CuS–Pt(iv ) NPs exhibits excellent antitumor effects upon NIR light irradiation.